The Rise in Norovirus-Related Acute Gastroenteritis During the Fight Against the COVID-19 Pandemic in Southern China - Lu, Ying; Zhang, Zhoubin; Xie, Huaping; Su, Wenzhe; Wang, Hui; Wang, Dahu; Lu, Jianyun (Frontiers in Public Health, 2022)
Abstract Background: There has been a significant decline in the morbidity of almost all infectious diseases during the COVID-19 pandemic. However, while the incidence of norovirus-related acute gastroenteritis declined in Guangzhou, China during the initial period of the pandemic, incidence increased significantly once the new school year began in September 2020. Methods: Norovirus-related acute gastroenteritis clusters and outbreaks were assessed in Guangzhou from 2015 to 2020. Medians and interquartile ranges were compared between groups using the Mann–Whitney U test, and attack rates were calculated. Results: While 78,579 cases of infectious diarrhea were reported from 2015 to 2019, with an average of 15,716 cases per year, only 12,065 cases of infectious diarrhea were reported in 2020. The numbers of sporadic cases and outbreaks reported from January to August 2020 were lower than the average numbers reported during the same time period each year from 2015 to 2019, but began to increase in September 2020. The number of cases in each reported cluster ranged from 10 to 70 in 2020, with a total of 1,280 cases and an average attack rate of 5.85%. The median number of reported cases, cumulative number of cases, and attack rate were higher than the average number reported each year from 2015 to 2019. The intervention time in 2020 was also higher than the average intervention time reported during 2015–2019. The main norovirus genotypes circulating in Guangzhou during 2015–2020 included GII.2 (n = 79, 26.69%), GII.17 (n = 36, 12.16%), GII.3 (n = 27, 9.12%), GII.6 (n = 8, 2.7%), GII.4 Sydney_2012 (n = 7, 2.36%), and GII.4 (n = 6, 2.03%). Conclusions: Findings illustrate the importance of maintaining epidemiological surveillance for viral gastroenteritis during the COVID-19 pandemic. Local disease prevention and control institutions need to devote sufficient human resources to control norovirus clusters.